Expression of chemokine receptors CXCR4, CCR2, CCR5 and CX(3)CR1 in neural progenitor cells isolated from the subventricular zone of the adult rat brain - Ji, JF (ELSEVIER IRELAND LTD, 2020)
10.1016/j.neulet.2003.11.024